2015
DOI: 10.1111/asj.12367
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clay on fat necrosis and carcass characteristics in Japanese Black steers

Abstract: Twenty 10-month-old Japanese Black steers were used to evaluate the effects of clay on fat necrosis and carcass characteristics. Ten steers (Clay group) were fed the clay (50 g/day) during 10-30 months of age. The other 10 steers (Control group) were not fed it. There was no significant difference in body weight or average daily gain between the two groups (P > 0.05). The occurrence of fat necrotic mass in the Clay group (30%) was lower (P < 0.05) than that in the Control group (90%) at slaughter. The size of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In fattening Wagyu cattle, obesity-associated adipose tissue disorders, called “fat necrosis” and “muscle inflammation”, occasionally develop during fattening periods [ 18 , 34 ]. The histological analysis of bovine fat necrosis shows an increasing fibrous area within visceral adipose tissue [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fattening Wagyu cattle, obesity-associated adipose tissue disorders, called “fat necrosis” and “muscle inflammation”, occasionally develop during fattening periods [ 18 , 34 ]. The histological analysis of bovine fat necrosis shows an increasing fibrous area within visceral adipose tissue [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…While it is a rare occurrence, its incidence is progressively increasing, leading to economic losses on farms [ 4 ]. A study conducted on Japanese black cattle in 2013 reported that around 1000 cattle per year were affected by fat necrosis, resulting in their disposal and further financial implications [ 18 ]. Unlike in humans where fat necrosis is not fatal and commonly occurs in the breast, in cattle it primarily affects the abdominal organs, often leading to intestinal obstruction and death [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that breed differences between Wagyu and Holsteins affect the macrophage infiltration and senescence state in visceral adipose tissue. In fattening Wagyu cattle, obesity‐associated adipose tissue disorders, called “fat necrosis,” occasionally develop in visceral adipose tissue (Ishida, Noda, Jomane, & Tokunaga, 2017; Oka, Iwamoto, & Tatsuda, 2015), characterized by an increase in the fibrous area within visceral adipose tissue (Ito, Miura, Ohshima, & Numakunai, 1968). Severe obese conditions accelerate macrophage infiltration and stimulate fibrosis of adipose tissue both in humans and rodents (Divoux et al., 2010; Kawanishi, Niihara, Mizokami, Yano, & Suzuki, 2013; Khan et al., 2009; Reggio, Pellegrinelli, Clement, & Tordjman, 2013).…”
Section: Discussionmentioning
confidence: 99%